The use of dual filial piety and self-acceptance intervention modules on meaning in life and self-regulation ability of Chinese college students: A literature review - Wenbo, Wang; Zakaria, Norazlina; Abdul Ghani, Mariny (Journal of Islamic, Social, Economics and Development, 2026)
Due to the characteristics of strict access and relatively flexible graduation in Chinese higher education, many college students experience difficulties in stimulating intrinsic learning motivation. After entering university, some students show reduced goal clarity, accompanied by declines in meaning in life (MIL) and self-regulation ability (SRA), which are associated with increased psychological distress. This review examines the major sources of MIL and the key influencing factors of SRA, and clarifies the theoretical rationale for considering approaches that integrate dual filial piety (DFP) and self-acceptance (SA). Drawing on a systematic review of the literature, the findings indicate that MIL and SRA emerge from the interaction between environmental contexts and individual psychological processes. By synthesizing evidence on core sources of MIL, including social relationships, self-identity, and value systems, as well as primary determinants of SRA, this review further examines the roles of DFP and SA and their associations with MIL and SRA. The literature suggests that DFP and SA function as culturally salient environmental and individual factors, respectively, closely linked to meaning construction and self-regulatory functioning among Chinese college students. Integrating these two constructs provides a theoretically grounded perspective for understanding MIL and SRA in this population and offers implications for future research and intervention development.